Food Standards and Exports : Evidence from China - Mangelsdorf, Axel; Portugal-Perez, Alberto; Wilson, John S. (2012)
Using a new database on Chinese food standards, this paper estimates the impact of volunta-ry and mandatory standards on its agricultural and food exports. The dataset covers seven Chinese products from 1992 to 2008. The findings here indicate that standards have a posi-tive effect on China's export performance. Standards signal to customers that products meet certain quality measures and promote information exchange. The benefits of increased ex-ports outweigh compliance costs. Our results also show that theses positive effects are larger when the standards are consistent with international norms.